2021
DOI: 10.3389/fimmu.2021.697313
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Horizons in Complement Analysis and Quality Control

Abstract: Complement not only plays a key role in host microbial defense but also modulates the adaptive immune response through modification of T- and B-cell reactivity. Moreover, a normally functioning complement system participates in hematopoiesis, reproduction, lipid metabolism, and tissue regeneration. Because of its powerful inflammatory potential, multiple regulatory proteins are needed to prevent potential tissue damage. In clinical practice, dysregulation and overactivation of the complement system are major c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 95 publications
0
21
0
2
Order By: Relevance
“…As more laboratories begin to adopt the use of biomarkers such as sC5b-9 in HSCT-TMA, testing capability and availability should improve [47,66,67]. Indeed, many groups, such as the International Union of Immunological Sciences and International Complement Society (IUIS/ICS) Committee for the Standardization and Quality Assessment in Complement Measurements, have been working in this direction [68]. Others have also suggested that biomarkers, such as the factor B activation product Ba, may show utility in HSCT-TMA [69].…”
Section: Hsct-tma: How Can It Be Identified?mentioning
confidence: 99%
“…As more laboratories begin to adopt the use of biomarkers such as sC5b-9 in HSCT-TMA, testing capability and availability should improve [47,66,67]. Indeed, many groups, such as the International Union of Immunological Sciences and International Complement Society (IUIS/ICS) Committee for the Standardization and Quality Assessment in Complement Measurements, have been working in this direction [68]. Others have also suggested that biomarkers, such as the factor B activation product Ba, may show utility in HSCT-TMA [69].…”
Section: Hsct-tma: How Can It Be Identified?mentioning
confidence: 99%
“…This need for standardization and well-defined and characterized assays is well-known within the field. It is therefore that in 2009, the Sub-Committee for the Standardization and Quality Assessment of Complement Measurements (the ‘Complement EQA Group’) was formally recognized and became part of the IUIS (International Union of Immunological Societies) Quality Assessment and Standardization Committee ( ) ( 2 , 82 ). Next to that, the Complement EQA Group is a standing committee also of the International Complement Society (ICS).…”
Section: Discussionmentioning
confidence: 99%
“…Next to that, the Complement EQA Group is a standing committee also of the International Complement Society (ICS). The purpose of the EQA group is to facilitate standardized diagnostic complement analysis by developing calibrator materials and test recommendations ( 2 , 82 ). Initial steps have been made as a serum standard to be used as calibrator for quantitative and functional complement analysis in normal, non-activated human serum (Standard 1; ICS#1) was prepared and evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations